2008
DOI: 10.1016/s0929-6646(08)60091-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Neonatal Outcome and Anthropometric Growth in Very Low Birth Weight Infants with Histological Chorioamnionitis

Abstract: Histological CAM was associated with a higher incidence of PPROM, sepsis, bronchopulmonary dysplasia, more mechanical ventilation and longer ventilation days. However, at the age of 2 years, CAM had no impact on anthropometric growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 21 publications
0
31
0
1
Order By: Relevance
“…Chorioamnionitis-exposed patients had either similar7 21 23 25 29 30 or decreased2 3 19 32 RDS incidences in most studies. While Elimian and colleagues reported an increase in RDS incidence, the difference disappeared after multivariate analysis 18.…”
Section: Respiratory Outcome After Chorioamnionitismentioning
confidence: 94%
“…Chorioamnionitis-exposed patients had either similar7 21 23 25 29 30 or decreased2 3 19 32 RDS incidences in most studies. While Elimian and colleagues reported an increase in RDS incidence, the difference disappeared after multivariate analysis 18.…”
Section: Respiratory Outcome After Chorioamnionitismentioning
confidence: 94%
“…Multiple clinical studies have shown that chorioamnionitis is strongly linked with an increased risk for the development of bronchopulmonary dysplasia (BPD) (14,22,40,41,45,48,53,64,66), which is the chronic lung disease of infancy that follows premature birth and injury to the immature lung. Despite improvements in perinatal care, BPD remains one of the most significant sequelae of prematurity (5).…”
mentioning
confidence: 99%
“…The percentage of CHA in our study was in the range of previously published studies. As shown in overview from Beer and Zimmerman (30), the increased incidence of BPD after prenatal inflammation was reproduced in 6 of 18 studies; furthermore, in only one study the results were adjusted for gestational age (31). Beside the importance of when the fetus is exposed to prenatal inflammation, the time of exposure to the intra-amniotic endotoxin is also important.…”
Section: Discussionmentioning
confidence: 96%